A comprehensive analysis and optimization process for an integrated liquid cooling plate for a prismatic lithium-ion battery module. (25th June 2019) - Chen, Siqi; Peng, Xiongbin; Bao, Nengsheng; Garg, Akhil
Highlights: Battery heat generation model is analysed with experiments to get thermal parameters. Temperature standard deviation is analysed in thermodynamics for heat uniformity. Maximum pressure, which affects running cost, is considered in fluid dynamics. Abstract: Thermal management of lithium-ion battery modules is essential to avoid thermal issues such as overheating and thermal runaway. Liquid-cooling is an efficient cooling method, and many publications can be found in this area. However, a parametric study on the influence of structural parameters on the cooling effect is still lacking. This article proposes a comprehensive way to quantitively evaluate the cooling effect of a liquid-cooled battery module. Computational fluid dynamics is used to establish the fluid-solid coupled heat dissipation model, using the thermal parameters values from experiments. Parameter combination samples are generated using the Latin Hypercubes method, and the effect of structural parameters on heat dissipation performance is determined using sensitivity analysis. Multi-Objective optimization is then performed to develop a cooling system with lower temperature and lower energy consumption. The optimized design is then verified by heat-dissipation experiments of a battery module set-up. The proposed method can be easily implemented in industrial battery pack manufacturing. The results show that with the same input power, the temperature reduction will be higher, 1.87 °C; and the temperature deviation can also be controlled within a small range, 0.35 °C.